Coronavirus Disease 2019 Pandemic Effects on Overseas Pakistanis Particularly Residing in China, Saudi Arabia and United Kingdom - Ahmad, Tauseef; Murtaza, Bibi Nazia; Ahmad, Faizan; Murad, Manal Abdulaziz; Baig, Mukhtiar; Imtiaz, Arouba; Baig, Fizzah; Baig, Javaria; Siraj, Muhammad; Sagga, Abdullah Khalid (Frontiers in Public Health, 2022)
Aim: This study explored the coronavirus disease 2019 (COVID-19) pandemic effects on overseas Pakistani's residing in various parts of the world, particularly in China, Saudi Arabia (SA), and the United Kingdom (UK). Methods: This cross-sectional study was completed between November 2020 and April 2021. An online questionnaire was designed and circulated via various social media mediums to overseas Pakistani communities. The obtained data were statistically analyzed through SPSS version 19 for windows. P-value less than 0.05 was considered statistically significant. Results: A total of 542 overseas Pakistani (157[29%] females and 385[71%] males) responded to the questionnaire. There were 174(32.1%), 142(26.45%), 117(21.6%), and 109(19.85%) participants from the UK, SA, China, and other countries, respectively. Many participants, or their family members, 93(17.2%), got infected with the coronavirus. About one-third, 165(30.4%), of the respondents were afraid that their company would violate their contracts or lose their jobs or be paid less. The majority, 469(86.5%), believed that the lockdown is increasing their psychological stress. More than half of the participants, 314(57.9%), stated that the Pakistani embassy did not facilitate them in their country of stay. About one-third, 194(35.8%), of the respondents faced visa-related issues. More than one-third of respondents, 221(40.8%), faced health issues due to a lack of physical activity during the lockdown. Males were afraid that their company would violate their contract, lose jobs, or be paid less than females (p<.001). Both genders had psychological stress and health issues because of the pandemic. The participants from SA faced more visa-related issues, and they were less satisfied with the efforts of the Pakistani embassy to facilitate them compared to the UK and China participants (p=.013). Conclusion: Our findings show that the COVID-19 pandemic impacted Pakistanis living in the UK, SA, China, and other parts of the world. They dealt with psychological stress, physical inactivity-related health issues, visa issues, and dissatisfaction with Pakistani embassy services. Pakistanis living abroad require government assistance to resolve their issues.